2017
DOI: 10.1080/17549507.2017.1287217
|View full text |Cite
|
Sign up to set email alerts
|

Probing morphological, syntactic and pragmatic knowledge through answers to wh-questions in children with SLI

Abstract: The experiment revealed that children with SLI did well on syntactic and pragmatic measures. The greatest challenge was in providing tense-related morphemes in their answers to questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Gibson et al, 2013), others say that the screening of pragmatic skills while evaluating the communication skills of individuals with SLI should be seriously considered (Osman et al, 2011). In fact, there are some pragmatic skills that are affected in individuals with SLI (or DLD), as the maxim of quantity in sentence answers to 'wh' questions (Rombough & Thornton, 2018). Also, Katsos et al (2011) confirmed that children with SLI do face difficulties in employing the maxim of informativeness as well as in understanding the logical meaning of quantifiers, and that these difficulties accompany their overall language difficulties.…”
Section: Sli (Or Dld) and Pragmaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibson et al, 2013), others say that the screening of pragmatic skills while evaluating the communication skills of individuals with SLI should be seriously considered (Osman et al, 2011). In fact, there are some pragmatic skills that are affected in individuals with SLI (or DLD), as the maxim of quantity in sentence answers to 'wh' questions (Rombough & Thornton, 2018). Also, Katsos et al (2011) confirmed that children with SLI do face difficulties in employing the maxim of informativeness as well as in understanding the logical meaning of quantifiers, and that these difficulties accompany their overall language difficulties.…”
Section: Sli (Or Dld) and Pragmaticsmentioning
confidence: 99%
“…SLI has been traditionally characterised as a deficit of structural language (specifically grammar) (Davies et al, 2016). Children with SLI frequently omit tense-related morphemes (Rombough & Thornton, 2018) and present weaknesses in noun and verb inflections at 5 years old. At pre-school age, number agreement is a major challenge for children with SLI, with difficulties especially in oral production of 'quantifier + noun', compared to 'determiner + noun' (Rice & Oetting, 1993).…”
Section: Sli and Syntaxmentioning
confidence: 99%